Potential Role of Natural Compounds Against Skin Aging - Tundis, R.; Loizzo, M.R.; Bonesi, M.; Menichini, F. (Current Medicinal Chemistry, 2015)
Skin aging is an inevitable biological phenomenon of human life. Advancing age brings changes to all components of the integumentary system with consequent signs on the skin. Skin aging is mainly due to intrinsic (chronologic) and extrinsic aging (photo-aging). Photo-aging is a consequence of exposure to ultraviolet radiations. Despite variable economic conditions, the skin care market based on natural products continues to see strong growth. In this context, the research of naturally occurring anti-aging agents is greatly expanding and in recent years numerous plant-derived products have been investigated. This review article focuses on highlighting recent advances in current knowledge on anti-aging natural products grouped and presented according to their family origin. Plants from 35 families were reviewed. A variety of phytomolecules, derived in particular from polyphenols, triterpenes and sterols classes, demonstrated a promising activity. Among them carnosic acid, curculigoside, curcumin, glycyrrhizic acid, mangiferin, mirkoin, asiaticoside, rosmarinic acid, tectorigenin, tyrosol etc., able to inhibit tyrosinase, hyaluronidase, elastase, and collagenase, to scavenge free radicals from skin cells, to prevent trans-epidermal water loss, and to contribute to protect skin from wrinkles, were largely investigated and herein discussed. Extracts and pure compounds from Fabaceae, Asperaceae and Zingiberaceae families have shown particular interest and appear most promising in the development of anti-aging products.
Keywords: Natural compounds